2010
DOI: 10.1097/tp.0b013e3181d2bfb2
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Was Associated With Inferior Outcomes in Simultaneous Pancreas Kidney Transplant

Abstract: BACKGROUND.: In kidney transplant, obesity was reported to be associated with increased posttransplant complications and worse survival outcomes. The impact of obesity in simultaneous pancreas-kidney (SPK) transplant is less known. METHODS.: Using Organ Procurement Transplantation Network/United Network for Organ Sharing data as of August 2008, we included all adults (>18 years) type 1 diabetic SPK recipients between years 2000 and 2007 with a pretransplant body mass index (BMI) of 18.5 to 40 kg/m. The cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 28 publications
6
46
1
1
Order By: Relevance
“…Risks for kidney and pancreas failure in overall insulin-dependent recipients were most importantly associated with AA race (versus Caucasian) and obesity (versus normal BMI). This was not a surprise because AA race was associated with increased risk of nonimmune and immune posttransplant complications (27), and obesity has been shown to be a potential risk for posttransplant complications in T1DM (28). In nontransplant surgery, obese patients were more likely to have increased surgical time and blood loss during the procedure (29,30).…”
Section: Discussionmentioning
confidence: 94%
“…Risks for kidney and pancreas failure in overall insulin-dependent recipients were most importantly associated with AA race (versus Caucasian) and obesity (versus normal BMI). This was not a surprise because AA race was associated with increased risk of nonimmune and immune posttransplant complications (27), and obesity has been shown to be a potential risk for posttransplant complications in T1DM (28). In nontransplant surgery, obese patients were more likely to have increased surgical time and blood loss during the procedure (29,30).…”
Section: Discussionmentioning
confidence: 94%
“…Sampaio et al (16) demonstrated that obesity in SPK recipients was found to be associated with an increased risk of posttransplant complications, pancreas and kidney graft loss, and patient death. They reported that poor outcomes in obese group were mainly caused by increased rates of delayed kidney graft function, 1-year kidney acute rejection, and pancreas graft thrombosis in obese recipients in comparison with normal recipients.…”
Section: Discussionmentioning
confidence: 98%
“…Large series have documented thrombosis to be responsible for the majority of technical failures and early gra loss [4,23]. Factors that have been shown to predispose to gra thrombosis include recipient obesity, preservation time, and nontraumatic causes of donor death [4,24].…”
Section: Discussionmentioning
confidence: 99%